Masculinity and Identity Crisis in the Secret Life of Walter Mitty (2013): A Hermeneutic Film Analysis - Ahmad Maulana; Yeni Prastiwi (ITScience (Information Technology and Science), 2026)
Socioeconomic transformations under neoliberalism have reshaped the construction of masculinity, moving it from traditional attributes to performance, visibility, and institutional recognition. This shift often generates identity instability, which is reflected in cultural texts such as film. This study aims to examine how masculinity and identity crisis are represented through the main character in The Secret Life of Walter Mitty (2013) using a hermeneutic approach. Using a qualitative method, the research analyzes six key scenes to interpret the relationships among narrative structure, dialogue, and visual symbolism. The findings reveal that Walter Mitty’s masculinity is initially marked by social invisibility, subordination, and reliance on fantasy as a compensatory mechanism for his lack of recognition. These fantasies construct an idealized but unstable masculine identity rooted in external validation. As the narrative progresses, Walter shifts from direct engagement with real-life experiences to risk-taking and self-reflection. His masculinity evolves into a more authentic and experiential form, grounded in personal awareness rather than institutional approval. The study demonstrates that masculinity in the film is not fixed but continuously negotiated between social expectations and individual agency. Ultimately, Walter’s transformation represents a critique of neoliberal pressures, highlighting a shift from performative masculinity to a more meaningful, self-defined identity.